2009
DOI: 10.12693/aphyspola.115.13
|View full text |Cite
|
Sign up to set email alerts
|

Kondo Lattice and Magnetic Properties in Strongly Correlated Electron Systems

Abstract: We review here the magnetic properties of some strongly correlated electron systems and especially cerium and uranium compounds. The normal Kondo lattice model with a localized S = 1/2 spin can account for the Kondo-magnetism competition observed in cerium or ytterbium systems, while the underscreened Kondo lattice model with a localized S = 1 spin can well account for the ferromagnetism -Kondo coexistence observed in some uranium compounds such as UTe. Then, we discuss the spin glass-Kondo competition and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The Kondo temperature T K becomes finite only above a critical value J The resulting "ferromagnetic-Kondo" diagram, which is given in Refs. [18,29], is completely different from the Doniach diagram derived for the Kondo lattice model appropriate for cerium or ytterbium compounds and represents really a new result for the study of magnetic actinide compounds.…”
Section: The Underscreened Kondo Lattice Model Applied To Uranium Commentioning
confidence: 71%
See 1 more Smart Citation
“…The Kondo temperature T K becomes finite only above a critical value J The resulting "ferromagnetic-Kondo" diagram, which is given in Refs. [18,29], is completely different from the Doniach diagram derived for the Kondo lattice model appropriate for cerium or ytterbium compounds and represents really a new result for the study of magnetic actinide compounds.…”
Section: The Underscreened Kondo Lattice Model Applied To Uranium Commentioning
confidence: 71%
“…Another conclusion is that the Kondo temperature for the lattice can be different and generally much smaller than the single-impurity one. The comparison with experiment is not easy, but it was suggested that such effets can be observed in cerium systems like CeRh 2 Si 2 compound [9,17,18].…”
Section: Introduction To Kondo Lattice Modelsmentioning
confidence: 99%
“…Our calculated magnetic moments for all three compounds, especially for CeS and CeTe, are unsatisfactory. The anomalous magnetic moment reduction and failure of DFT to describe it well might be related to the role of Kondo screening which cannot be accounted for in DFT [13,14] or the f-band hybridization, f-band Coulomb exchange, and crystal field interactions which can be better explained with Hamiltonian systems with ab initio determined parameters [9]. To further elucidate the magnetic structure, we include strong correlation effects by repeating the calculations mentioned above in the GGA + framework for = 2, 4, 6 eV and display the resulting relative energy and structural and magnetic parameters as function of in Figures 1 and 2, respectively.…”
Section: Lattice Structure and Magneticmentioning
confidence: 99%
“…Often these systems contain Ce, Yb, U or Np as one of their constituents, implying that 4f or 5f electrons are involved. Characteristics examples are: 3 , 2 2 , 2 2 , 6 , 3 , 2 2 etc [Coqblin, 2009]. Below a characteristics temperature (usually on the order of a few Kelvin up to a few tens of Kelvin) heavyfermion systems show Fermi-liquid behavior with large effective masses of the quasiparticles.…”
Section: Introductionmentioning
confidence: 99%